Perovskite quantum dot glass as well as preparation method and application thereof
By coating the titanium dioxide or silica shell on the surface of perovskite quantum dot glass particles and heat treatment, a stable shell structure is formed, which solves the instability of perovskite quantum dot glass in humid and hot environment, and significantly improves the Its humidity and heat and thermal blue light stability are suitable for optoelectronic products.
Patent Information
- Application Number
- CN202310764629.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
AI Technical Summary
Perovskite quantum dot glass is unstable in humid and hot environments, and is prone to react with water molecules to cause structural damage, affecting its performance in optoelectronic products such as displays.
The surface of perovskite quantum dot glass particles is coated with a dense titanium dioxide or silica shell, and a stable shell structure is formed by heat treatment to improve its moisture and heat stability and thermal blue light stability.
Effectively block the erosion of the hydrothermal environment on the glass network, improve the humidity and heat stability and thermal blue light stability of perovskite quantum dot glass, and extend its service life.
Smart Images

Figure CN119193153A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite quantum dots, and in particular relates to a perovskite quantum dot glass and a preparation method and application thereof. Background Art
[0002] Inorganic CsPbX3 perovskite quantum dots have excellent optical properties, including high quantum yield, high color purity and tunable emission spectra. They are considered to be a highly promising material in the field of optoelectronics and one of the most promising photoelectric conversion materials for next-generation displays. Unfortunately, perovskite halide materials are extremely unstable when exposed to moisture, heat and blue light. The inorganic amorphous glass network has abundant gap space, and the compact / robust glass network structure helps to isolate the perovskite quantum dots from the external environment, thereby improving the stability of the perovskite quantum dots. However, the glass structure is relatively brittle, easy to break and not easy to form a film, which is not conducive to display applications. Therefore, in practical applications, the quantum dot glass needs to be broken and ground into micron-sized powder and then prepared into a film. During the crushing and grinding process, the structure of the glass surface is greatly destroyed, resulting in the quantum dot glass composite material The barrier effect of water in a thermal environment is greatly weakened. Water molecules react directly with the silicon-oxygen skeleton on the surface of the quantum dot glass structure (hydration reaction). As the hydration reaction proceeds, the original four bridging oxygen bonds around the Si atom all become -OH, forming Si(OH)4, thereby directly destroying the quantum dot glass network structure.
[0003] Therefore, improving the water stability of perovskite quantum dot glass powder is an issue that needs to be urgently addressed on the road to the industrialization of perovskite quantum dot glass. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a perovskite quantum dot glass and a preparation method and application thereof. The perovskite quantum dot glass has excellent thermal stability, blue light stability and wet heat stability.
[0005] In one aspect of the present invention, the present invention provides a perovskite quantum dot glass. According to an embodiment of the present invention, it includes:
[0006] a core comprising perovskite quantum dot glass particles;
[0007] The shell is coated on the core, and the shell comprises at least one of titanium dioxide and silicon dioxide.
[0008] The perovskite quantum dot glass according to the above embodiment of the present invention includes a core and a shell, wherein the core includes perovskite quantum dot glass particles, and the shell is coated on the core, and the composition of the shell includes at least one of titanium dioxide and silicon dioxide. By coating a dense shell on the surface of the perovskite quantum dot glass particles, the hydrothermal environment is effectively blocked from eroding the glass network on the surface of the perovskite quantum dot glass powder, thereby improving the wet heat stability of the perovskite quantum dot glass, and at the same time, the perovskite quantum dot glass coated with the above shell continues the thermal and blue light stability of the glass quantum dots. As a result, the perovskite quantum dot glass has excellent thermal, blue light stability and wet heat stability.
[0009] In addition, the perovskite quantum dot glass according to the above embodiment of the present invention may also have the following technical features:
[0010] In some embodiments of the present invention, the particle size of the core is 0.5 μm to 20 μm. Thus, the wet-heat stability of the perovskite quantum dot glass can be improved.
[0011] In some embodiments of the present invention, the thickness of the shell is 0.5 nm to 300 nm. Thus, the wet-heat stability of the perovskite quantum dot glass can be improved.
[0012] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned perovskite quantum dot glass. According to an embodiment of the present invention, the method comprises:
[0013] (1) mixing glass raw materials and quantum dot precursor raw materials, grinding them, and then sintering them to obtain a perovskite quantum dot glass precursor;
[0014] (2) grinding the perovskite quantum dot glass precursor to obtain perovskite quantum dot glass precursor powder;
[0015] (3) mixing the perovskite quantum dot glass precursor powder, the first solvent and the coating solvent, stirring and centrifuging to obtain a quantum dot glass precipitate;
[0016] (4) The quantum dot glass precipitate is subjected to heat treatment in sequence, wherein the heat treatment includes at least a first heat treatment and a second heat treatment, to obtain perovskite quantum dot glass.
[0017] The glass raw material and the quantum dot precursor raw material are mixed evenly and then ground, and then sintered to obtain a perovskite quantum dot glass precursor. The quantum dots in the above perovskite quantum dot glass precursor have not yet precipitated. Then the perovskite quantum dot glass precursor is ground to obtain a perovskite quantum dot glass precursor powder that meets film-forming conditions. The above perovskite quantum dot glass precursor powder, the first solvent and the coating solvent are mixed and stirred to form a coating shell layer on the perovskite quantum dot glass precursor powder. Then, the quantum dot glass precipitate is centrifuged to obtain a first heat treatment and a second heat treatment. The quantum dot glass precipitate is sequentially subjected to a first heat treatment and a second heat treatment. The first heat treatment breaks the internal stress of the glass so that the ions in the quantum dot precursor can migrate. The second heat treatment allows the quantum dots to migrate and aggregate with the help of energy provided by the outside world, and finally nucleates and crystallizes, thereby obtaining a perovskite quantum dot glass. At the same time, because of the first heat treatment and the second heat treatment, the above coating shell layer is calcined to form a dense shell structure, which further improves the wet heat stability of the perovskite quantum dot glass. Therefore, the method can be used to prepare perovskite quantum dot glass with excellent thermal stability, blue light stability and wet heat stability.
[0018] In addition, the method for preparing perovskite quantum dot glass according to the present invention may also have the following technical features:
[0019] In some embodiments of the present invention, in step (1), the grinding time is 10 min to 20 min.
[0020] In some embodiments of the present invention, in step (1), the sintering temperature is 1100° C. to 1300° C., and the sintering time is 8 min to 15 min. Thus, a perovskite quantum dot glass precursor can be obtained.
[0021] In some embodiments of the present invention, in step (2), the grinding time is 15 min to 30 min.
[0022] In some embodiments of the present invention, in step (2), the particle size of the perovskite quantum dot glass precursor powder is 10 μm to 300 μm.
[0023] In some embodiments of the present invention, in step (3), the coating solvent includes at least one of isopropyl titanate, tetraethyl titanate, tetrabutyl titanate, tetraisobutyl titanate (containing isopropoxy), tetra(2-ethylhexyl) orthotitanate, APTES and tetramethoxysilane. Thus, the wet-heat stability of the perovskite quantum dot glass can be improved.
[0024] In some embodiments of the present invention, the first solvent includes at least one of ethanol, toluene, trimethylbenzene, dichloromethane and ethyl acetate.
[0025] In some embodiments of the present invention, in step (4), the temperature of the first heat treatment is 300° C. to 400° C., and the time is 2 h to 8 h. Thus, the wet heat stability of the perovskite quantum dot glass can be improved.
[0026] In some embodiments of the present invention, the temperature of the second heat treatment is 450° C. to 550° C., and the time is 6 h to 15 h. Thus, the wet heat stability of the perovskite quantum dot glass can be improved.
[0027] In a third aspect of the present invention, the present invention proposes the use of the above-mentioned perovskite quantum dot glass or the perovskite quantum dot glass prepared by the above-mentioned method in optoelectronic products.
[0028] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0030] Figure 1 Schematic diagram of the structure of the perovskite quantum dot glass according to an embodiment of the present invention, wherein 100 is the core and 200 is the shell;
[0031] Figure 2 This is a graph showing the aging performance test results of the perovskite quantum dot glass obtained in Examples 1-7 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0032] The embodiments of the present invention are described in detail below, which are intended to explain the present invention but should not be construed as limiting the present invention.
[0033] In one aspect of the present invention, the present invention provides a perovskite quantum dot glass. According to an embodiment of the present invention, reference is made to Figure 1 The perovskite quantum dot glass comprises: a core 100 and a shell 200, wherein the core 100 comprises perovskite quantum dot glass particles, the shell 200 is coated on the core 100, and the composition of the shell 200 comprises at least one of titanium dioxide and silicon dioxide.
[0034] The inventors found that by coating the surface of the perovskite quantum dot glass particles with a dense shell 200, the hydrothermal environment is effectively blocked from eroding the glass network on the surface of the perovskite quantum dot glass powder, thereby improving the wet heat stability of the perovskite quantum dot glass. At the same time, the perovskite quantum dot glass coated with the shell 200 continues the thermal and blue light stability of the glass quantum dots. As a result, the perovskite quantum dot glass has excellent thermal, blue light stability and wet heat stability. It should be noted that the perovskite quantum dot glass particles refer to the perovskite quantum dot glass in the form of small particles of powder formed by grinding the perovskite quantum dot glass.
[0035] According to an embodiment of the present invention, the particle size of the core 100 is 0.5 μm to 20 μm. The inventors found that if the particle size of the core 100 is too large, there will be serious self-absorption in the process of preparing the optical film and the polydimethylsiloxane film (PDMS film), resulting in a low quantum yield; if the particle size of the core 100 is too small, the larger the surface area, the more the structure of the quantum dots is exposed on the surface, and more and more quantum dot A, B, and X elements are exposed to the outside and even decomposed because there are no ligand quantum dots. Therefore, the present application uses a core 100 with a particle size of 0.5 μm to 20 μm to improve the wet heat stability of the perovskite quantum dot glass.
[0036] According to an embodiment of the present invention, the thickness of the shell 200 is 0.5nm to 300nm. The inventors found that if the thickness of the shell 200 is too small, the coated shell layer is not dense, and the performance of improving the wet heat stability of the quantum dot glass powder is poor; if the thickness of the shell 200 is too large, the outer shell layer is too thick and opaque, thereby reducing the quantum yield of the quantum dots. Therefore, the present application adopts a shell with a thickness of 0.5nm to 300nm, which can improve the wet heat stability of the perovskite quantum dot glass.
[0037] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned perovskite quantum dot glass. According to an embodiment of the present invention, the method comprises:
[0038] S100: Glass raw materials and quantum dot precursor raw materials are mixed, ground and sintered
[0039] In this step, the glass raw material and the quantum dot precursor raw material are mixed evenly, and fully ground for 10 minutes to 20 minutes, and then placed in a closed chamber for sintering to obtain a perovskite quantum dot glass precursor. The above grinding time cannot be too long, otherwise the powder will absorb water, and the water will destroy the perovskite. In order to avoid the powder absorbing water, the above grinding can be carried out in a vacuum environment or an environment with a protective gas. It should be noted that the glass raw materials and quantum dot precursors are conventional materials in this field and are not particularly limited here. Furthermore, the sintering temperature is 1100-1300°C and the time is 8 minutes to 15 minutes. The inventors found that if the sintering time is too short or the temperature is too low, the quantum dot glass raw material will not be completely melted, and a uniform molten state will not be achieved. The quantum dot components will not volatilize enough, and the final quantum dot product will have an incorrect fluorescence quantum yield (PLQY) or emission peak position. If the sintering time is too long or the sintering temperature is too high, the quantum dot glass components will volatilize excessively, causing an element that makes up the quantum dots to volatilize excessively, which will cause the quantum dots to be unable to crystallize in the glass matrix or the components to be missing, resulting in a shorter wavelength. Thus, the quantum dot glass precursor is fired, and the quantum dot glass block is obtained by annealing and heat treatment after grinding or directly annealing and heat treatment.
[0040] S200: Grinding the Perovskite Quantum Dot Glass Precursor
[0041] In this step, the perovskite quantum dot glass precursor prepared in S100 is cooled and then ground, so that the perovskite quantum dot glass precursor is ground into a perovskite quantum dot glass precursor powder of the particle size required for subsequent film making. It should be noted that grinding is a conventional operation, and the grinding equipment or tools are not particularly limited here. Furthermore, the grinding time is 15min to 30min, and the particle size of the obtained perovskite quantum dot glass precursor powder is 10μm to 300μm, preferably 10μm to 20μm.
[0042] S300: Mix the perovskite quantum dot glass precursor powder, the first solvent and the coating solvent and centrifuge
[0043] In this step, the perovskite quantum dot glass precursor powder prepared in S200, the first solvent and the coating solvent are mixed and stirred, and the coating solvent is hydrolyzed to form a coating shell on the perovskite quantum dot glass precursor powder, and then centrifuged to obtain a quantum dot glass precipitate. Further, the coating solvent includes at least one of isopropyl titanate, tetraethyl titanate, tetrabutyl titanate, tetraisobutyl titanate (containing isopropoxy), tetra(2-ethylhexyl) orthotitanate, APTES (H2NCH2CH2CH2Si(OC2H5)3) and tetramethoxysilane. It should be noted that the first solvent is a conventional real reagent in the field, and those skilled in the art can select it according to actual conditions. For example, the first solvent includes at least one of ethanol, toluene, trimethylbenzene, dichloromethane and ethyl acetate. Further, the mixing and stirring time is 3h to 8h, and the rotation speed is 500rad / min to 700rad / min. If the stirring time is too long, a large amount of water may be introduced into the coating material during the hydrolysis process, resulting in the destruction of the coated outer layer structure and the original glass-coated quantum dot structure.
[0044] S400: Heat treatment of quantum dot glass precipitation
[0045] In this step, the quantum dot glass precipitate obtained in S300 is dried and placed in a muffle furnace for the first heat treatment. After the first heat treatment is completed, the temperature is directly raised for the second heat treatment, thereby obtaining perovskite quantum dot glass. The first heat treatment breaks the internal stress of the glass, allowing the ions in the quantum dot precursor to migrate, and the second heat treatment allows the quantum dots to migrate and aggregate with the help of energy provided by the outside world, and finally nucleate and crystallize, thereby obtaining perovskite quantum dot glass. At the same time, because of the first heat treatment and the second heat treatment, the above-mentioned coating shell layer is calcined to form a dense shell structure, further improving the wet heat stability of the perovskite quantum dot glass.
[0046] According to an embodiment of the present invention, the temperature of the first heat treatment is 300℃~400℃, and the time is 2h~8h. The inventors found that if the temperature of the first heat treatment is too high and the time is too long, the quantum dots can directly nucleate and crystallize and grow out at this stage, without the nucleation accumulation stage of the glass quantum dots, which is not conducive to the regulation of the performance of the quantum dot glass; if the temperature of the first heat treatment is too low and the time is too short, the perovskite quantum dot glass cannot nucleate, which in turn affects the crystallization of the quantum dot glass in the next stage, and ultimately affects the optical properties of the quantum dot glass product. Therefore, the present application adopts the first heat treatment condition of a temperature of 300℃~400℃ and a time of 2h~8h, which can improve the wet heat stability of the perovskite quantum dot glass.
[0047] According to an embodiment of the present invention, the temperature of the second heat treatment is 450℃~550℃, and the time is 6h~15h. The inventors found that if the temperature of the second heat treatment is too high and the time is too long, the quantum dots inside the glass network structure will undergo Ostwald ripening transition growth, the emission will be red-shifted, the particle size will increase, and the quantum yield will be low; if the temperature of the second heat treatment is too low and the time is too short, the quantum dots will not grow completely, the emission peak will be blue-shifted, and there will be many defects, and the quantum dot glass will have poor performance. Therefore, the present application adopts the second heat treatment condition of 450℃~550℃ and 6h~15h, which can improve the wet heat stability of perovskite quantum dot glass.
[0048] In a third aspect of the present invention, the present invention proposes the use of the above-mentioned perovskite quantum dot glass or the perovskite quantum dot glass prepared by the above-mentioned method in optoelectronic products. Specifically, it can be applied to backlight luminescent materials for display, perovskite quantum dot films, and fluorescent conversion layer materials for lighting.
[0049] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0050] Example 1
[0051] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber like a furnace for sintering. The sintering temperature is 1200℃ and the time is 10min, so as to obtain a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 0.5mL of tetrabutyl titanate, stir for 30min at an open 600rad / min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510℃ and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 0.5nm to 100nm.
[0052] Example 2
[0053] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber for sintering at a temperature of 1200℃ for 10min, thereby obtaining a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 0.5mL of isopropyl titanate, stir for 30min at an open 600rad / min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510 degrees Celsius and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 0.5nm to 100nm.
[0054] Example 3
[0055] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber for sintering at a temperature of 1200℃ for 10min, thereby obtaining a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 0.5mL of tetraisobutyl titanate (containing isopropoxy), stir at an open 600rad / min for 30min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510 degrees Celsius and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 0.5nm to 100nm.
[0056] Example 4
[0057] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate) -8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber for sintering at a temperature of 1200℃ for 10min, thereby obtaining a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 0.5mL of tetra(2-ethylhexyl) orthotitanate, stir for 30min at an open 600rad / min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510℃ and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 0.5nm to 100nm.
[0058] Example 5
[0059] Weigh 9g of raw materials with a glass raw material and quantum dot raw material ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15 minutes, and then place them in a closed chamber like a furnace for sintering at a temperature of 1200℃ for 10 minutes to obtain a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30 minutes. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 0.1mL APTES (H2NCH2CH2CH2Si(OC2H5)3), stir at 600rad / min for 30 minutes and centrifuge. The above centrifuged precipitate was placed in a muffle furnace for heat treatment, first at 400°C for 5 hours, then continued to heat up to 510°C for 10 hours. After heating, titanium ore quantum dot glass with silicon dioxide coated titanium ore quantum dot glass particles was obtained. The core particle size of the obtained perovskite quantum dot glass particles was 10 microns, and the thickness of the silicon dioxide shell was 0.1 to 20 nm.
[0060] Example 6
[0061] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber like a furnace for sintering. The sintering temperature is 1200℃ and the time is 10min, so as to obtain a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 3mL of tetrabutyl titanate, stir for 30min at an open 600rad / min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510℃ and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 100nm to 300nm.
[0062] Example 7
[0063] Weigh 9g of the raw materials of glass raw materials and quantum dot raw materials in the ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF, mix them evenly, grind them thoroughly for 15min, and then place them in a closed chamber like a furnace for sintering. The sintering temperature is 1200℃ and the time is 10min, so as to obtain a perovskite quantum dot glass precursor; grind the cooled quantum dot glass powder precursor material in a mortar for 30min. Take 1g of quantum dot glass powder precursor and add it to 15mL of ethanol solution, then add 10ml of tetrabutyl titanate, stir for 30min at an open 600rad / min and centrifuge. Take the above centrifuged precipitate and put it into a muffle furnace for heat treatment, first keep it at 400℃ for 5h, and then continue to heat it to 510℃ and keep it for 10 hours. After heating, titanium dioxide coated titanium ore quantum dot glass particles are obtained. The core particle size of the obtained perovskite quantum dot glass particles is 10 microns, and the thickness of the titanium dioxide shell is 200nm to 1000nm.
[0064] Comparative Example 1
[0065] 9 g of raw materials with a glass raw material and quantum dot raw material ratio of 34B2O3-38SiO2-8ZnO-3C4H6O4Sr (strontium acetate)-8Cs2CO3-4PbBr2-5KBr-5NaF were weighed and mixed evenly, and fully ground for 15 minutes, and then placed in a closed chamber for sintering at a temperature of 1200°C for 10 minutes, thereby obtaining a perovskite quantum dot glass precursor; the cooled quantum dot glass precursor was placed in a muffle furnace for heat treatment, first at 400°C for 5 hours, and then continued to heat up to 510 degrees Celsius for 10 hours. After the annealing heat treatment is completed, a bright perovskite quantum dot glass under 365nm ultraviolet light can be obtained.
[0066] The properties of the perovskite quantum dot glasses obtained in Examples 1-7 and Comparative Example 1 were measured.
[0067] (1) PLQY test of perovskite quantum dot glass powder: 0.045 g quantum dot glass powder was weighed, 2 g PDMS glue was added and mixed evenly, degassed, dried at 85 °C for 30 min, and a PDMS film was prepared. The PLQY of the PDMS film was tested, which was the PLQY of the quantum dot glass powder. The specific results are shown in Table 1.
[0068] (2) The aging performance of the PDMS membrane was tested by the wet heat method: the PDMS membrane was placed in a 65°C / 95% humidity environment and its PLQY change over time was measured as the aging test effect. The specific test results are shown in Figure 2 ,in Figure 2 The ordinate is the ratio of the PLQY of the PDMS film during the aging test to the PLQY of the PDMS film before the aging test.
[0069] Table 1
[0070]
[0071] From Table 1 and Figure 2 It can be seen that the perovskite quantum dot glass of the present application has a good quantum yield. As the wet heat time increases, the quantum yield of the quantum dot glass without shell protection in comparative example 1 decreases rapidly, while the quantum yield of the perovskite quantum dot glass of Examples 1-7 is relatively stable, indicating that the perovskite quantum dot glass of the present application exhibits excellent wet heat stability.
[0072] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
Claims
1. A perovskite quantum dot glass, characterized in that: include: a core comprising perovskite quantum dot glass particles; The shell is coated on the core, and the shell comprises at least one of titanium dioxide and silicon dioxide.
2. The perovskite quantum dot glass according to claim 1, characterized in that: The particle size of the core is 0.5 μm to 20 μm.
3. The perovskite quantum dot glass according to claim 1 or 2, characterized in that: The thickness of the shell is 0.5nm-300nm.
4. A method for preparing the perovskite quantum dot glass according to any one of claims 1 to 3, characterized in that: include: (1) mixing glass raw materials and quantum dot precursor raw materials, grinding them, and then sintering them to obtain a perovskite quantum dot glass precursor; (2) grinding the perovskite quantum dot glass precursor to obtain perovskite quantum dot glass precursor powder; (3) mixing the perovskite quantum dot glass precursor powder, the first solvent and the coating solvent, stirring and centrifuging to obtain a quantum dot glass precipitate; (4) subjecting the quantum dot glass precipitate to heat treatment, wherein the heat treatment comprises at least a first heat treatment and a second heat treatment, so as to obtain perovskite quantum dot glass.
5. The method according to claim 4, characterized in that In step (1), the grinding time is 10 min to 20 min; Optionally, the sintering temperature is 1100° C. to 1300° C., and the sintering time is 8 min to 15 min.
6. The method according to claim 4, characterized in that In step (2), the grinding time is 15 min to 30 min; Optionally, the particle size of the perovskite quantum dot glass precursor powder is 10 μm to 300 μm.
7. The method according to claim 4, characterized in that In step (3), the coating solvent includes at least one of isopropyl titanate, tetraethyl titanate, tetrabutyl titanate, tetraisobutyl titanate (containing isopropoxy), tetra(2-ethylhexyl) orthotitanate, APTES and tetramethoxysilane; Optionally, the first solvent includes at least one of ethanol, toluene, trimethylbenzene, dichloromethane and ethyl acetate.
8. The method according to claim 4, characterized in that In step (4), the temperature of the first heat treatment is 300°C to 400°C, and the time is 2h to 8h.
9. The method according to claim 4, characterized in that In step (4), the temperature of the second heat treatment is 450°C to 550°C, and the time is 6h to 15h.
10. Use of the perovskite quantum dot glass according to any one of claims 1 to 3 or the perovskite quantum dot glass prepared by the method according to any one of claims 4 to 9 in optoelectronic products.
